High seebeck coefficient in middle-temperature thermocell with deep eutectic solvent - Naura Fakhira Antariksa (Nature Portfolio, 2021)
Abstract Deep eutectic solvent (DES) was applied to the solvent of thermocell and high Seebeck coefficient (S e) of the thermocell was achieved at high-temperatures operation. The S e of a redox couple of ferricyanide and ferrocyanide ([Fe(CN)6]3−/4−) reaches − 1.67 mV/K in a DES consisting of ethylene glycol and choline chloride. Spectroscopic analysis reveals that this is due to the strong interactions between the redox couple and the DES. Furthermore, the cell can operate over a wide temperature range of 135–165 °C. This result is a desired feature for waste-heat recovery applications.